2016
DOI: 10.1097/acm.0000000000001252
|View full text |Cite
|
Sign up to set email alerts
|

Professional Identity Formation and the Clinician–Scientist: A Paradigm for a Clinical Career Combining Two Distinct Disciplines

Abstract: The clinician-scientist role is critical to the future of health care, and in 2010, the Carnegie Report on Educating Physicians focused attention on the professional identity of practicing clinicians. Although limited in number, published studies on the topic suggest that professional identity is likely a critical factor that determines career sustainability. In contrast to clinicians with a singular focus on clinical practice, clinician-scientists combine two major disciplines, clinical medicine and scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 32 publications
0
26
0
3
Order By: Relevance
“…Early training for physician–scientists must not only develop trainees’ foundational knowledge, investigative skills, and the ability to publish and write grants but must also give them intra- and interpersonal skills to persist in a challenging though rewarding career. 36 There is a risk of attrition at each level of professional transition. The PSTP curriculum, which includes mentoring and training in writing, critical review of the literature, and statistical analysis, is designed to build persistence; however, early phases of our curriculum did not explicitly address skills in time management or in dealing with the unpredictability of funding, 2 of the challenges that PSTP students and graduates identified as barriers to persisting in a physician–scientist career.…”
Section: Discussionmentioning
confidence: 99%
“…Early training for physician–scientists must not only develop trainees’ foundational knowledge, investigative skills, and the ability to publish and write grants but must also give them intra- and interpersonal skills to persist in a challenging though rewarding career. 36 There is a risk of attrition at each level of professional transition. The PSTP curriculum, which includes mentoring and training in writing, critical review of the literature, and statistical analysis, is designed to build persistence; however, early phases of our curriculum did not explicitly address skills in time management or in dealing with the unpredictability of funding, 2 of the challenges that PSTP students and graduates identified as barriers to persisting in a physician–scientist career.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein and with an individual focus, Rosenblum et al [ 43 ] have recently tried to define the nature of clinician-scientist professional identity to understand the underlying motivations and actions that underlie the decision to enter this career track and to remain a clinician-scientist, claiming that understanding the challenges of being a clinician-scientist might contribute to greater career sustainability. With a similar focus on the individual level, it has been suggested that physician scientists need special encouragement and tools in order to balance clinical and research duties as well as balancing (personal) life and career [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, the ability to identify a mentor was significantly associated with academic career intentions and with interest in translational and clinical research by multivariate regression analysis. In addition to cultivating research interest, previous studies have argued that early and persistent mentorship may help address specific concerns from trainees regarding physician-scientist identity formation, as well as the challenges faced by physician-scientists within academia [38]. In this regard, a diverse and dedicated cohort of physician-scientist mentors appears to be a critical determinant of the success of efforts to cultivate a diverse next generation of physician-scientists [39].…”
Section: Mentorshipmentioning
confidence: 99%